Usaha dan Pengembangan Industri Kecil Berbasis Komunitas Lokal - Fachry Noviar Singka; Nurmala K. Panjaitan; Tjahja Muhandri (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2014)
House of Balikpapan Creative (RKB) is a small and medium industry that has been developed and focuses on hand made batik and recycle handicraft. This small industry involves local community that consists of disability people and housewife. The existence of RKB is formed by oil and gas company contribution to local community in their operations area through Corporate Social Responsibility program. Current condition of RKB needs development strategy systematically. This research is aimed toreview the current state of business, to review the performance and to formalize the business development strategy of RKB in an attempt to increase the independence and sustainability of the business. Data collection was done through observation; interviewand focus group discussion as well as disseminating a questionnaire to 30 respondents, which used RKB products. The data is analyzed descriptively where as IPA analyzes performance review. Internal Factor Evaluation Matrix, External Factor Evaluation Matrix, Internal External Matrix, Strength, Weakness, Opportunities and Threats (SWOT) Matrix Analysis along with Quantitative Strategy Planning Matrix (QSPM) analyze strategy development. Outcome mapping performance and consumer interests described the RKB need to allocate adequate resources for improving the performance of the product in terms of price, speed orders, precision workers and handling complaints and media promotion. Based on the SWOT and QSPM analysis, the most major strategic priorities which need to be implemented are organizational restructuring and management system, increase promotion, partnering with banking institutions, sets the market price strategy to confront the competition, improve the quality of service to customers.